Differences in Spending by Local Trail Users: Two-Part Model of Expenditures. Issue 1 (2016) - Ermagun, Alireza; Lindsey, Greg
Urban multiuse trails are the backbones of nonmotorized transportation networks in metropolitan areas across the United States. These trails provide opportunities for recreation and utilitarian travel, increase access to important destinations, and serve other public purposes. A common rationale for trail development is that users spend money and support retail businesses in trail corridors. Expenditures by local trail users do not constitute new regional economic impacts but are important locally and of interest to planners and business owners who view trails as mechanisms to spur local economic activity. The results of intercept surveys completed by 1, 282 trail users on the Central Ohio Greenway trail network in 2014 were used to estimate the probabilities and patterns that different types of trail users will make expenditures. Approximately one-fifth of trail users reported spending between 15.00 and 20.00 for food, drink, and other incidental items. Across all trail users the average expenditure by individuals was about 3.00 per visit. All else equal, cyclists were more than twice as likely as other users to report expenditures. Users visiting trails principally for recreation were 53% more likely to spend, while users visiting trails mainly for exercise were about 19% less likely. Longer trips to and on the trails were associated with higher spending. These results can be used to inform local planning, marketing, and economic development activities related to local trail networks.